Flow cytometric analysis of gut mucosal lymphocytes supports an impaired Th1 cytokine profile in spondyloarthropathy. Issue 5 (1st May 2001) - Van Damme, N; De Vos, M; Baeten, D; Demetter, P; Mielants, H; Verbruggen, G; Cuvelier, C; Veys, E M; De Keyser, F
Abstract : OBJECTIVE: To quantify the fraction of gut mucosal lymphocytes expressing the T helper type 1 (Th1) cytokines, interferon γ (IFNγ) and interleukin (IL)2, and the Th2 cytokines, IL4 and IL10, at the single cell level in patients with spondyloarthropathy (SpA) in comparison with healthy controls. METHODS: An improved extraction protocol was used for the enrichment of intraepithelial lymphocytes (IELs) and lamina propria lymphocytes (LPLs) from colonic and ileal biopsy specimens obtained from patients with SpA (n=20) and healthy controls (n=13). After stimulation with phorbol ester/ionomycin, expression of the intracellular cytokines IFNγ, IL2, IL4, and IL10 was determined in CD3+, CD3+CD8+ and CD3+CD8− T cells by flow cytometry. RESULTS: In colonic LPLs, a significant decrease in IFNγ-producing CD3+ cells was observed (p=0.02) in patients with SpA. In the CD3+CD8− subset, the proportion of cells producing IFNγ and IL2 was decreased in patients with SpA (p=0.021 and p=0.027 respectively). In ileal LPLs, the percentage of IL10-producing CD3+CD8− cells was significantly increased (p=0.046). CONCLUSION: An impaired Th1 cytokine profile is observed in gut mucosal lymphocytes from patients with SpA. This adds to the existing evidence that the gut mucosal immune apparatus is involved in the pathogenesis of SpA.